DETERMINAN LOYALITAS MAHASISWA - Emi Wardati (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study examines the effect of determinant factors of student loyalty.Population in this study were students in STIE Totalwin Semarang.Based on purposive sampling method, 240 samples were obtained byobservation data. The results of this study indicate that studentssatisfaction, students trust, students commitment, and students perceptionabout learning has significant influence on student loyalty